VIOLATIONS OF INTERNATIONAL HUMANITARIAN LAW BY ISRAEL IN RETALIATORY ATTACKS AGAINST HAMAS AND THE GLOBAL RESPONSE - Mellinda Raswari Jambak; Anwar Masadi; Alam An Shori (Arabic Literature Department, 2025)
The attack launched by Hamas against Israel, rooted in a long-standing historical conflict dating back to 1948, culminated in the events of October 7, 2023. Israel’s military response to the attack has sparked widespread debate, particularly regarding potential violations of international humanitarian law. This study aims to provide an in-depth analysis of the legal violations committed by Israel during its retaliatory attacks against Hamas, as well as the international community’s response. The research adopts a normative juridical approach, referencing primary legal sources from international humanitarian law governing armed conflict, and is supported by secondary literature such as books, accredited academic journals, and scholarly articles. Data were collected through document studies and literature reviews, and analyzed through data reduction, presentation, and conclusion drawing. The findings reveal that Israel has violated several fundamental principles of international humanitarian law, including the principles of humanity, proportionality, distinction, and military necessity. International responses appear polarized; most European countries expressed support for Israel, while many Asian and Arab nations condemned its actions due to the significant impact on civilian populations. This polarization reflects a growing imbalance in the application of humanitarian principles in the context of armed conflict.